1980
DOI: 10.1530/jrf.0.0600059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of  -chlorohydrin on glucose metabolism by spermatozoa from the cauda epididymidis of the rhesus monkey (Macaca mulatta)

Abstract: Summary. Spermatozoa from the cauda epididymidis of the rhesus monkey had metabolic properties similar to those published for ejaculated spermatozoa. The concentration of glycolytic intermediates was low until 2 mM-glucose was added; glucose 6-phosphate, fructose 1,6-bis-phosphate and the triose phosphates then increased but glycerate 3-phosphate did not. It was concluded that the activity of glyceraldehyde 3-phosphate dehydrogenase (EC 1.2.1.12) limited flux through the glycolytic pathway. The production of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Similar effects have been observed when ram and rhesus monkey spermatozoa were incubated with (R,S)-cx-chlorohydrin (Brown-Woodman et al 1978;Ford and Harrison 1980) but the present study is' the first to demonstrate that it is the (S)-isomer that is effective and that the (R)-isomer is devoid of any inhibitory activity. Furthermore, the degree of inhibition observed on ram and rhesus monkey spermatozoa was not as marked indicating that boar spermatozoa are more susceptible to the inhibitory action of (S)-cx-chlorohydrin than are those from the other species.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar effects have been observed when ram and rhesus monkey spermatozoa were incubated with (R,S)-cx-chlorohydrin (Brown-Woodman et al 1978;Ford and Harrison 1980) but the present study is' the first to demonstrate that it is the (S)-isomer that is effective and that the (R)-isomer is devoid of any inhibitory activity. Furthermore, the degree of inhibition observed on ram and rhesus monkey spermatozoa was not as marked indicating that boar spermatozoa are more susceptible to the inhibitory action of (S)-cx-chlorohydrin than are those from the other species.…”
Section: Discussionsupporting
confidence: 83%
“…Inhibition by (R,S)-cx-chlorohydrin of the oxidation of fructose or glucose to COz by rat, ram, boar, rhesus monkey and human spermatozoa in vitro has been well established (Hommonai et al 1975;Brown-Woodman et al 1978;Ford et al 1979;Ford and Harrison 1980;Hutton et al 1980). In the present study, this inhibitory effect on the metabolism of boar spermatozoa has been shown to be confined to the (S)-isomer of cx-chlorohydrin.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Low doses (2.5-10 mg/kg/day) of a-chlorohydrin (3-chloropropan-1,2-diol) induced reversible male infertility in several mammalian species, including rat [16, Cauda epididymal spermatozoa from animals given low doses of a-chlorohydrin break down glucose and fructose less rapidly than the spermatozoa from controls [17,20,311. When spermatozoa from untreated animals are incubated in vitro with low concentrations of a-chlorohydrin (< 1 mM), glycolysis is greatly reduced [15,19,311; this failure is accompanied by a rapid decrease in motility and ATP content of the inhibited cells compared with controls [ l l , 171.…”
Section: Energy Metabolism and Sperm Motilitymentioning
confidence: 99%